THE DEMAND AND INTERESTS OF YOUNG PEOPLE IN BOOKS TODAY - Berdiqulova Muqaddam Muxtorali qizi (Web of Journals Publishing, 2025)
This article explores the shifting demand and interests of young people in books, focusing on the types of genres, formats, and themes that resonate with them today. The study examines various factors influencing their reading habits, including technological advancements, social media, and education. By analyzing the current trends in young people's book preferences, the article provides insights into how the publishing industry and educators can adapt to these changes. The findings highlight the importance of understanding the evolving nature of youth interests in literature and its implications for both the future of reading and education.
Keywords: Young people, book demand, reading habits, literature preferences, technology, social media, publishing industry, education.